PERSEPSI MASYARAKAT DAN DAYA DUKUNG PERAIRAN BAGI KEGIATAN BUDIDAYA PERIKANAN DI KAWASAN DANAU PONDOK LAPAN DUSUN PULKA KECAMATAN SALAPIAN KABUPATEN LANGKAT - Meyna Melia Utari; Pindi Patana; Febrina Arli (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2016)
Pondok Lapan Lake is an artificial lake located at Dusun Pulka Desa Naman Jahe Kecamatan Salapian Kabupaten Langkat. Pondok Lapan Lake around palm plantations. The lake was originally made for irrigation, but the surrounding communities prefer to gardening such as palm oil and rubber. Pondok Lapan Lake has untapped potential optimally in aquaculture activities. The study focused on public perception and the carrying capacity of water for aquaculture activities. This study was conducted in July until August 2015. Sampling using purposive sampling by conducting interviews and questionnaires. This study resulted in that community to support the activities of aquaculture cages if done at Pondok Lapan Lake as much as 82.8% (Very Agree), the remaining 17.2% (Very Disagree) and the public know the activities of aquaculture cages ever do in Pondok Lapan Lake by 74% (Known) while the remaining 26% (Unknown). Suitability carrying on Pondok Lapan Lake can accommodate aquaculture activities as much as 14 cages with a size of 4x4x2 m3 and aquaculture systems Keramba Plug (KJT).Keywords: Pondok Lapan Lake, Carrying Capacity of Water, Public Perception